50 Jahre Kritik an der deutschen Zahlungsbilanz - Anton Konrad (Wirtschaftsdienst, 2014)
Die Debatte über Leistungsbilanzungleichgewichte in der Eurozone mündete im November 2013 in ein Prüfverfahren der EU-Kommission gegen Deutschland. Das Ergebnis lautet, dass der anhaltend hohe Überschuss in der deutschen Leistungsbilanz das Funktionieren der Eurozone gefährde. Anton Konrad zeigt auf, dass der amerikanische Nationalökonom Charles P. Kindleberger bereits 1965 verschiedene Erklärungen für den anhaltenden deutschen Zahlungsbilanzüberschuss diskutiert hat. – – For nearly 50 years Germany has been criticised for the surplus on its balance of payments, especially on the current account. In 1965 and 1976, Charles P. Kindleberger analysed this phenomenon and predicted its persistence. The causes he presented were structural (the structure of German exports, a special "propensity to export" the docility of German labour, German innovation and technical progress) and macroeconomic (inflation abroad, the German propensities to save or not to absorb); institutional factors were responsible for an inadequate long-term capital export so that the export surplus led to an accumulation of foreign liquid assets. It is shown that these forces, with some modifications, are still prevalent. Instead of alleviating these problems, the European Economic and Monetary Union reinforced the tendency towards disequilibrium.
Keywords: E61; F41; F42; 330; Außenwirtschaftliches Gleichgewicht; Eurozone; Leistungsbilanz; Deutschland